Jalinan Cinta dan Keadilan - Mulyatno, C.B. (Jurnal Orientasi Baru, 2007)
Industrialized society has been greatly driven by major economical and political powers. Science and technology, human resources, competition, social welfare, political participation and tolerance are widely discussed topics. Meanwhile "non-commercial" issues such as human dignity, love, justice, solidarity and social responsibility have been very much down-toned. Pragmatism was introduced consistently and through the insistence of massmedia propaganda a new way of life was born with marks of materialism, hedonism, consumerism and individualism. Undermining others and reality of the progressive natural destruction show the existence of the so-called â€culture of death". Sadly, injustice and violence have been globalized. Amid these situations, love, justice and social responsibility have to be reflected seriously and reintroduced.